Policy levers to increase jobs and increase income from work after the Great Recession - David Neumark (IZA Journal of Labor Policy, 2016)
The depth of the Great Recession, the slow recovery of job creation, the downward trend in labor force participation, high long-term unemployment, stagnant or declining wages for low-to-medium skill jobs owing to adverse labor demand shifts, and a greater rebound in low-wage than mid- or higher-wage jobs raised concerns that the normal business cycle dynamics of recovery from the recession will be insufficient to offset the diminished labor market prospects of many workers. These concerns have spurred serious consideration of policies to encourage job creation and higher income from work beyond the more immediate countercyclical policies that were adopted in response to the Great Recession. Among the policies generating continuing or renewed interest are hiring credits, higher (sometimes much higher) minimum wages, and a more substantial earned income tax credit (EITC) for childless individuals. This paper discusses these policy options, what we know about their likely effects and trade-offs, and what the unanswered questions are; the focus is on US evidence.
Keywords: J2; J3; J6; 330; Hiring credits; Wage subsidies; Minimum wage; Earned income tax credit